English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Since it is not in the form of quadratic equation , you have to make it into such an equation.

2007-02-09 03:25:12 · 1 answers · asked by p 1 in Science & Mathematics Mathematics

1 answers

(x-a)/(x-b) + (x-b)/(x-a) = a/b +b/a
multiply x-a
(x-a)^2/(x-b) + (x-b) = (a/b +b/a)(x-a)
multiply x-b
(x-a)^2 + (x-b)^2 =(a/b +b/a)(x-a)(x-b)
(x-a)^2 - (a/b +b/a)(x-a)(x-b) + (x-b)^2 = 0

[(x-a)-(a/b)(x-b)] [(x-a)-(b/a)(x-b)] = 0

So, (x-a)-(a/b)(x-b)=0
b(x-a)-a(x-b)=0
(b-a)x=0
x=0 where a<>b

So, (x-a)-(b/a)(x-b)=0
a(x-a)-b(x-b)=0
(a-b)x=a^2-b^2
(a-b)x=(a+b)(a-b)
x = a+b
where a<>b

2007-02-09 03:39:51 · answer #1 · answered by seah 7 · 2 0

fedest.com, questions and answers